Could sudden sensorineural hearing loss be the sole manifestation of COVID-19? An investigation into SARS-COV-2 in the etiology of sudden sensorineural hearing loss (2020)
Objective: This study aimed to investigate the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in patients presenting with only sudden sensorineural hearing loss (SSHNL) during the COVID-19 pandemic. Methods: The study included five male patients who presented with the sole complaint of unilateral SSNHL to the otolaryngology outpatient clinic between 03–12 April 2020. The patients were referred to the infectious diseases clinic to be evaluated for SARS-CoV-2 by real time polymerase chain reaction (RTPCR) testing. Results: RT-PCR testing for SARS-CoV-2 was positive in one of the patients and negative in the other four patients. A positive response to COVID-19-specific treatment in the SARS-CoV-2 positive SSNHL patient was noted. Conclusion: It should be remembered that non-specific symptoms such as SSNHL could be the only sign with which to recognize a COVID-19 case. Awareness of such a non-specific presentation of COVID-19 patients is crucial during this pandemic period for preventing infectious spread through isolation and early initiation of COVID-19 targeted treatment.